2011
DOI: 10.12659/msm.881976
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose effect of DNA repair-related gene expression in mouse white blood cells

Abstract: SummaryBackgroundThe aim of this study was to screen molecular biomarkers for biodosimetry from DNA repair-related gene expression profiles.Material/MethodsMice were subjected to whole-body exposure with 60Co γ rays with a dose range of 0–8 Gy at a dose rate of 0.80 Gy/min. RNA was extracted from the peripheral blood of irradiated mice at 4, 8, 12, 24 and 48hrs post-irradiation. The mRNA transcriptional changes of 11 genes related to DNA damage and repair were detected using real-time quantitative polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…As X‐irradiation mostly causes DSB, we focused on genes known to be involved in DSB‐repair. ATM, which is known to play an important role as a sensor of DNA–DSBs and leads to the induction of DNA‐repair mechanisms by attracting other DNA‐repair genes (Li, Wang, Chen, Shen, & Min, ), was significantly upregulated (FC = 4.5 ± 1.07) in irradiated microglia compared to nonirradiated microglia and spleen CD45 high ‐expressing cells (FC = −1.2 ± 0.28). In brain CD45 high ‐expressing cells, ATM could not be detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As X‐irradiation mostly causes DSB, we focused on genes known to be involved in DSB‐repair. ATM, which is known to play an important role as a sensor of DNA–DSBs and leads to the induction of DNA‐repair mechanisms by attracting other DNA‐repair genes (Li, Wang, Chen, Shen, & Min, ), was significantly upregulated (FC = 4.5 ± 1.07) in irradiated microglia compared to nonirradiated microglia and spleen CD45 high ‐expressing cells (FC = −1.2 ± 0.28). In brain CD45 high ‐expressing cells, ATM could not be detected.…”
Section: Resultsmentioning
confidence: 99%
“…As X-irradiation mostly causes DSB, we focused on genes known to be involved in DSB-repair. ATM, which is known to play an important role as a sensor of DNA-DSBs and leads to the induction of DNArepair mechanisms by attracting other DNA-repair genes (Li, Wang, Chen, Shen, & Min, 2011), was significantly upregulated (FC 5 4.5 6…”
Section: Significant Upregulation Of Atm a Dna-double Strand Breakmentioning
confidence: 99%
“…DNA repair is a biological pathway affected by ionization radiation. In previous studies, the expression level of RAD51 was reported in human lymphocytes in response to radiation ( 15 , 23 , 24 ); however, there has been no in vivo biological dosimetry study for the RAD51 gene at different radiation doses using real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of gene copies was performed using the ABI 7300 Real-Time PCR system (Applied Biosystems; Thermo Fisher Scientific, Inc.) with the Power SYBR ® Green PCR Master Mix kit (Promega Corporation). The primer sequences used were as follows: Forward, 5'-GCA CAC GGA TTG CTC AAG GA-3' and reverse, 5'-GCC CAT TCG GAA TAT GGA TCAG-3' for ATM (14); and forward, 5'-CAA TGA CCC CTT CAT TGA-3' and reverse, 5'-GAC AAG CTT CCC GTT CTC AG-3' for GAPDH (15). The following thermocycling conditions were used: An initial predenaturation step at 95˚C for 10 min, followed by 40 cycles of denaturation at 95˚C for 15 sec and annealing at 60˚C for 60 sec.…”
Section: Methodsmentioning
confidence: 99%